Le maschere senza volto. Gli eroi “tragici” del nouveau roman - Andrea Chiurato (Between, 2017)
As many other experimental writers of the XX century, the nouveaux romanciers have paid a particular attention to the role and the scope of the tragedy in the modern world. By questioning its conceptual and prototypical structures they thus wished to understand its everlasting influence on our civilisation and, at the same time, to undercover its ideological underpinnings. That’s perhaps the reason behind their fascination for the long vexed questions related to status of the tragic hero in the contemporary age; the same questions which, since the beginning of the Fifties, aroused a heated debate among themselves.